Origen y evolución del complejo volcánico Cerro Prieto, Baja California Norte - García Sánchez, Laura (Universidad Michoacana de San Nicolás de Hidalgo, 2014)
The Cerro Prieto Volcanic Complex (CPVC) is located ~ 30 km SE of Mexicali and west of the Cerro Prieto Geothermal Field (CPGF), Baja California Norte. It sits on a pull-apart basin that belongs to the transtensional tectonic system that includes the San Andres Fault System and the Salton Trough basin to the NW and the Eastern Pacific Dorsal to the SE. In this work seven stratigraphic units were recognized. 40Ar/39Ar dating of two of these units suggested that volcanic activity of the complex was initiated ~ 77,000 years ago with the extrusion of a basal. The activity continued with the emission of domes and a dyke that were destroyed by a phreatic explosion that emplaced a fall deposit and excavated a 300 m wide and 40 m deep crater. The activity migrated ~ 650 m to the SW with the emission of three lava domes and a final fissure lava flow. CPVC has been subjected to remobilization of volcanic material by water generating debris and hyperconcentrated flows in the surrounding terrain. Petrographic and geochemical analyses indicates that the CPVC erupted calc-alkaline magmas of dacitic composition (65.6-68.9 wt. % SiO2), generally, of aphanitic texture with phenocrysts of plg + opx + Ti-Fe ox + qtz. The composition of plagioclase varies from An31Ab50Or0.5 to An49Ab65Or3 and orthopyroxene from En44Fs30Wo3 to En58Fs50Wo4, with #Mg values between 36 and 39. As for the Fe-Ti oxides, titanomagnetite predominates over ilmenite.

El Complejo Volcánico Cerro Prieto (CVCP) se ubica a ~30 km al SE de Mexicali y al oeste del Campo Geotérmico Cerro Prieto (CGCP) en Baja California Norte. El CVCP es parte del sistema tectónico transtensivo que comprende el Sistema de Fallas de San Andrés al NO, la provincia tectónica “Salton Trough” con el Campo Geotérmico de “Salton Sea” en Estados Unidos y el “pull-apart” de Cerro de Cerro Prieto en México y la Dorsal del Pacifico Oriental al SE. En este trabajo se reconocieron siete unidades estratigráficas. Fechamientos de 40Ar/39Ar de dos de las unidades indican que el CVCP se formó hace ~ 77 mil años con la extrusión de una lava basal. El vulcanismo continuó con la emisión de domos y un dique que fueron destruidos por una explosión freática que emplazó un depósito de caída y excavó un cráter de 300 m de diámetro y 40 m de espesor. La actividad migró ~ 650 m al SO con la emisión de tres domos de lava y un flujo de lava fisural. El CVCP ha estado expuesto a la remoción de material volcánico por lluvias, lo que ha generado flujos de escombros e hiperconcentrados en la planicie circundante. El estudio petrográfico y geoquímico indica que el CVCP emitió lavas calcialcalinas de composición dacítica (65.6-68.9 wt. % SiO2), por lo general, de textura afanítca con fenocristales de plg + opx + ox de Fe-Ti + qz. La composición química de las plg varía de An31Ab50Or0.5 a An49Ab65Or3 y la de los opx varía de En44Fs30Wo3 a En58Fs50Wo4, con un valor de #Mg entre 36 y 39. En cuanto a los óxidos de Fe-Ti, es más predominante la titanomagnetita.
Instituto de Investigación en Metalurgia y Materiales. Maestría en Geociencias y Planificación del territorio
Keywords: info:eu-repo/classification/cti/1; IIMM-M-2014-0288; Estratigrafía; Petrografía; Geoquímica; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5211